Adsorption of Lead and Methylene Blue by Oudemansiella radicata - He, Nan; Liu, Yingyi; Li, Bo; Jiang, Juan; Xu, Heng (Asian Journal of Chemistry, 2013)
Oudemansiella radicata was employed as an adsorbent to adsorb lead and methylene blue from aqueous solution. Response surface methodology and mixture design were both applied to exploring the competitivity and different ratio between lead and methylene blue. The results showed that lead had an obvious inhibition to methylene blue, but methylene blue had little effect on lead on the contrary. The isotherm and kinetic analysis presented that the Freundlich model can explain the adsorption of lead in both single and mixture system and methylene blue only in mixture system. The pseudo-second-order kinetic model best described the kinetic of the adsorption process of lead and methylene blue in single and mixture system. The adsorption of methylene blue also fitted Elovich kinetic model.